2021
DOI: 10.1111/os.12921
|View full text |Cite
|
Sign up to set email alerts
|

Joint Awareness after Patellofemoral Arthroplasty Evaluated with the Forgotten Joint Score: A Comparison Study

Abstract: Objective The aim of the present study was to compare the forgotten joint score (FJS) in patients with isolated patellofemoral osteoarthritis who underwent patellofemoral arthroplasty (PFA) versus those who underwent total knee arthroplasty (TKA) and to analyze the predictors of the FJS after PFA. Methods From January 2014 to December 2017, a retrospective cohort study of 56 consecutive patients with isolated patellofemoral osteoarthritis underwent PFA and were included in the PFA group. The patients in the PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Two systematic reviews also found similar PROM scores between second-generation PFA and TKA 71,72 . However, some individual studies have shown higher postoperative PROMs and range of motion with PFA when compared to TKA, 73 including a randomized controlled trial by Odgaard et al in 2018 74 . With a sample size of 100 patients randomized to TKA or PFA, they found higher PROMs, better range of motion, and better overall quality of life in the PFA group.…”
Section: Resultsmentioning
confidence: 99%
“…Two systematic reviews also found similar PROM scores between second-generation PFA and TKA 71,72 . However, some individual studies have shown higher postoperative PROMs and range of motion with PFA when compared to TKA, 73 including a randomized controlled trial by Odgaard et al in 2018 74 . With a sample size of 100 patients randomized to TKA or PFA, they found higher PROMs, better range of motion, and better overall quality of life in the PFA group.…”
Section: Resultsmentioning
confidence: 99%
“…FJS can measure a patients' ability to forget joint awareness in daily life. Lin et al reported that patients who underwent PFA had a significantly higher FJS than those who underwent TKA ( 44 ). The average FJS was 71.2 ± 10.2 in our study at the last follow-up, indicating that the patient had been able to forget joint awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Patellofemoral arthroplasty may become necessary, particularly in elderly patients, with advanced patellofemoral arthritis and gross destruction of the joint [ 40 ] (Fig. 8 ).…”
Section: Surgical Treatmentmentioning
confidence: 99%